Well Preserved Bamboo Exploration As a Beam Stimulation - Denesh, K.C.; Hameed, A. Abdul; Venkatesh, S. Gnana; Mani Kandhan, K.U. (International Journal of Psychosocial Rehabilitation, 2019)
In this modern world, India is one of the fast growing countries in technology as well as infrastructure. Due to an intense rapid growth in infrastructure the demand of resources for construction has reached its peak. Steel is the major component for high rise buildings, Sky scrapers and modern structural elements etc. Steel is soared and expensive. But the infrastructure cannot be stopped because of the steel. So Bamboo is an alternative reinforcement material instead of steel. Bamboo is introduced in concrete after investigating and studying its physical and mechanical properties. The demand for these materials is also less in rural areas since it is one of the fast growing grasses. Bamboo is fully replaced with steel reinforcement. The reinforcement cannot be done with the whole bamboo for small cross section elements in construction. So it is bisected into clums and tied with binding wires. The main aim to introduce bamboo as reinforcement is preferably cost and readily available raw material. This bamboo was the basic construction material in olden days even before cement was introduced. It does not need any investment of money and time where it easily grows and easy to transport. Bamboos can be highly recommended for the rural areas where low rise buildings are raised and with cheaper rates. Steel reinforcement was used for seismic activity and tensile property. But the manufacturing and transport cost is expensive. So an alternate is introduced and is also investigate whether it is suitable for the replacement with lower cost. This paper investigates the feasibility of bamboo reinforcement for concrete beams. If steel is replaced with bamboo then the behavior of the structure is observed and results are recorded for improving the enhancement of the structure